2021
DOI: 10.5812/ijhls.113242
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Death Anxiety, and the Related Factors in Nurses Caring for COVID-19 Patients at Kosar Hospital, Semnan, Iran

Abstract: Background: The high incidence of COVID-19 has provided a challenge for healthcare systems in Iran, and may result in some psychological problems. Objectives: The study aims at describing depression, death anxiety, and the related factors in nurses caring for COVID-19 Patients at Kosar Hospital, Semnan, Iran. Methods: In this cross-sectional study, 89 nurses caring for COVID-19 patients were selected in October 2020 via the census method. A demographic questionnaire, Beck’s Depression inventory, and Templer De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…Similar findings were reported by Rouhi et al, (2015) [46], Tavakkoli et al, (2021) [47], and Aghajani et al, (2010) [18]. In contrast, Nobahar et al,'s (2021) study demonstrated a relationship between death anxiety and age contrary to the present study [48].…”
Section: │ Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were reported by Rouhi et al, (2015) [46], Tavakkoli et al, (2021) [47], and Aghajani et al, (2010) [18]. In contrast, Nobahar et al,'s (2021) study demonstrated a relationship between death anxiety and age contrary to the present study [48].…”
Section: │ Discussionsupporting
confidence: 87%
“…This discrepancy may stem from differences in the age of study subjects, cultural influences, and the research environment. No statistically significant relationships were found between death anxiety and other qualitative demographic variables, including marital status, education level, and the occurrence of a family member's earth's disease, aligning with the findings of Nobahar et al, (2021) [48]. The study underscores the importance of training, evaluating the effectiveness of educational processes, and conducting needs assessments to enhance the quality-of-care services [5].…”
Section: │ Discussionsupporting
confidence: 82%
“…The rate of death anxiety in this sample is 62.7%, with other research also reporting high rates, such as 53.2% in China in the general population ( Zhang et al., 2020 ) or 80% in physicians in Latin America ( Indacochea –Cáceda et al., 2021 ). The high levels of PPD symptoms, health anxiety and death anxiety found in this study, coupled with the fact that previous research has found that depression is associated with both health anxiety ( Kibbey et al., 2021 ; Uçar et al., 2015 ;) and death anxiety ( Nobahar et al., 2021 ; Semenova and Stadtlander, 2016 ), suggest that both are a vulnerability factor for postpartum psychological distress.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, for mothers, there is an additional level of vulnerability caused by pregnancy and childbirth, for example, research suggests that mothers who have just given birth have a shattered sense of self-esteem ( Hutchinson and Cassidy, 2021 ), while the COVID-19 pandemic seriously limited personal interactions, encouraged social distancing, and discouraged new mothers from engaging in close interpersonal relationships. As death anxiety is associated with depression ( Nobahar et al., 2021 ; Semenova and Stadtlander, 2016 ) and as women tend to manifest higher death anxiety than men ( Wong, 2012 ), this increases in death anxiety during the COVID-19 pandemic may put mothers at increased risk for PPD symptomatology. Furthermore, literature shows significant negative correlations between death anxiety and wellbeing ( Mansori et al., 2018 ).…”
Section: Health Anxiety and Death Anxietymentioning
confidence: 99%
See 1 more Smart Citation